Bangladesh Society of Medical Microbiologists Executive Committee 2011 2013 (Bangladesh Journal of Medical Microbiology, 2013)
DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15819 Bangladesh J Med Microbiol 2011; 05 (01)